2008
DOI: 10.1007/s00467-007-0635-7
|View full text |Cite
|
Sign up to set email alerts
|

Simple multicystic dysplastic kidney disease: end points for subspecialty follow-up

Abstract: Simple multicystic dysplastic kidney (MCDK) disease, defined as unilateral MCDK without other genitourinary tract involvement, portends an excellent prognosis. Nevertheless, its long-term management remains undefined. This study aims to provide subspecialty discharge recommendations for these patients. We identified eighty patients with simple MCDK disease by renal ultrasound between 1996 and 2006. Their charts were reviewed for growth of the contralateral kidney, involution of the MCDK, and incidence of compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 17 publications
2
24
1
2
Order By: Relevance
“…However, children with involuted MCDK are rarely followed into adulthood to assess GFR, proteinuria, or hypertension [40]. Some authors have suggested that follow-up is not necessary if there is involution of MCDK, contralateral renal hypertrophy, and normal renal function by the first year of life [41]. Our study indicates that children with contralateral abnormalities are at risk for developing decreased kidney function.…”
Section: Discussionmentioning
confidence: 64%
“…However, children with involuted MCDK are rarely followed into adulthood to assess GFR, proteinuria, or hypertension [40]. Some authors have suggested that follow-up is not necessary if there is involution of MCDK, contralateral renal hypertrophy, and normal renal function by the first year of life [41]. Our study indicates that children with contralateral abnormalities are at risk for developing decreased kidney function.…”
Section: Discussionmentioning
confidence: 64%
“…Weinstein et al followed 80 MCDK patients for a mean of 5 years and asserted that the favourable criteria of contralateral hypertrophy, ipsilateral involution and freedom from hypertension, chronic renal insufficiency or urinary tract infection are often met by 1 year of age. Discharge from subspecialty follow-up at this time would preclude repeated visits, uncomfortable investigations and unnecessary costs [23]. Our proposed schedule of follow-up should minimise such legitimate concerns, but a longer follow-up will be required in the majority of cases as only 35 % of patients in our series had involuted completely by 2 years, 47 % by 5 years and 62 % by 10 years.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, Godbole et al 29 state that the routine estimation of GFR is not required in the follow-up of children undergoing unilateral nephrectomy for benign disease if the contralateral kidney appears normal on imaging. Weinstein et al 30 even suggest that specific nephrological follow-up in children with MCDK could be ceased as soon as the length of the contralateral kidney has reached or grown beyond the 95% CI.…”
Section: Discussionmentioning
confidence: 99%